1976
DOI: 10.3133/pp963
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of the south flank of Kilauea Volcano; the result of forceful intrusion of magma into the rift zones

Abstract: Seismic evidence has long indicated that the south flank of Kilauea Volcano is mobile. Examination of triangulation, trilateration, and leveling data obtained throughout the 20th century shows that the south flank of Kilauea has been displaced upward and away from the rift zones by as much as several metres. The amount of horizontal displacement approximates the probable amount of dilation that accompanies the intrusion of magma as dikes in the rift zones and is greatest for p~riods of most intense intrusive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
204
0
2

Year Published

1977
1977
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(222 citation statements)
references
References 16 publications
16
204
0
2
Order By: Relevance
“…La polaridad de progresión de la actividad volcá-nica en la fractura en la erupción de 1730 podría deberse a que, a niveles ya muy superficiales, se superpongan dos mecanismos: Por una parte un proceso autoalimentado que obliga a la fractura, una vez iniciada su apertura por el efecto de cuña de la presión hidráulica del magma (Swanson et al, 1976;Hardee, 1982), a progresar en un sentido, originando un plano de ruptura intercalado forzadamente entre los di-ques que componen el eje estructural con un frente de avance de bajo ángulo en la dirección de propagación, lo que haría que el conducto eruptivo intersectase a la superficie en lugares cada vez más alejados del punto inicial de emisión.…”
Section: Cuarta Fase: Mñas Del Fuegounclassified
“…La polaridad de progresión de la actividad volcá-nica en la fractura en la erupción de 1730 podría deberse a que, a niveles ya muy superficiales, se superpongan dos mecanismos: Por una parte un proceso autoalimentado que obliga a la fractura, una vez iniciada su apertura por el efecto de cuña de la presión hidráulica del magma (Swanson et al, 1976;Hardee, 1982), a progresar en un sentido, originando un plano de ruptura intercalado forzadamente entre los di-ques que componen el eje estructural con un frente de avance de bajo ángulo en la dirección de propagación, lo que haría que el conducto eruptivo intersectase a la superficie en lugares cada vez más alejados del punto inicial de emisión.…”
Section: Cuarta Fase: Mñas Del Fuegounclassified
“…The prevolcanic oceanic crust, located at about 7 km depth and lubricated by an accumulation of deep-sea sediments, has been suggested as the slide plane [Furumoto and Kovach, 1978;Crosson and Endo, 1982;Lipman et al, 1985]. Swanson et al [1976] noted that the entire south flank of Kilauea is mobile and had undergone extensions of several meters in the la.st century previous to the 1975 earthquake. On the basis of displacement measurements, seismicity, and field observations, they concluded that the zone of dilatation or "tear-away zone" separating the south flank from the remaining volcano is composed of the southwest ri(t zone; the east rift zone, and the Koae fault system (see Figure 1).…”
Section: Previous Studies Of the Kalapana Earthqyakementioning
confidence: 99%
“…Hawaii is one of the most seismically active regions in the world and has been serving as a natural laboratory for studying the interactions between seismic and magmatic processes for the past few decades [e.g., Swanson et al, 1976;Lipman et al, 1985;Hill and Zucca, 1987;Rubin et al, 1998;Cayol et al, 2000;Hill et al, 2002;Amelung et al, 2007;Brooks et al, 2008]. The U.S. Geological Survey Hawaiian Volcano Observatory (HVO) operates an extensive seismic network (pink triangles in Figure 1) to measure and study the ongoing activity on the Island of Hawaii.…”
Section: Introductionmentioning
confidence: 99%